Robotic Stroking on the Face and Forearm: Touch Satiety and Effects on Mechanical Pain - Taneja, Pankaj; Baad-Hansen, Lene; Shaikh, Sumaiya; Svensson, Peter; Olausson, Håkan (Frontiers in Pain Research, 2021)
Background: Slow stroking touch is generally perceived as pleasant and reduces thermal pain. However, the tactile stimuli applied tend to be short-lasting and typically applied to the forearm. This study aimed to compare the effects of a long-lasting brushing stimulus applied to the facial region and the forearm on pressure pain thresholds (PPTs) taken on the hand. Outcome measurements were touch satiety and concurrent mechanical pain thresholds of the hand. Methods: A total of 24 participants were recruited and randomized to receive continuous stroking, utilizing a robotic stimulator, at C-tactile (CT) favorable (3 cm/s) and non-favorable (30 cm/s) velocities applied to the right face or forearm. Ratings of touch pleasantness and unpleasantness and PPTs from the hypothenar muscle of the right hand were collected at the start of stroking and once per minute for 5 min. Results: A reduction in PPTs (increased pain sensitivity) was observed over time (P < 0.001). However, the increase in pain sensitivity was less prominent when the face was stroked compared to the forearm (P = 0.001). Continuous stroking resulted in a significant interaction between region and time (P = 0.008) on pleasantness ratings, with a decline in ratings observed over time for the forearm, but not on the face. Unpleasantness ratings were generally low. Conclusion: We observed touch satiety for 5 min of continuous robotic brushing on the forearm confirming previous studies. However, we did not observe any touch satiety for brushing the face. Mechanical pain sensitivity, measured in the hand, increased over the 5-min period but less so when paired with brushing on the face than with brushing on the forearm. The differential effects of brushing on the face and forearm on touch satiety and pain modulation may be by the differences in the emotional relevance and neuronal pathways involved.